Tinjauan Green Tourism Dalam Perspektif Hukum Pariwisata - Jelly N. Sendow (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The understanding of the concept of green tourism from the perspective of tourism law in Indonesia is the objective of this study. Green tourism, also known as eco-tourism, is a sustainable tourism concept that emphasizes a balance between environmental conservation, energy efficiency, and the social welfare of surrounding communities. Based on a normative juridical approach, which includes legislation, literature, and related documents, it shows that the concept of green tourism is not explicitly regulated in national law. However, in principle, it is reflected in Law Number 10 of 2009 concerning Tourism, Law Number 32 of 2009 concerning Environmental Protection and Management, as well as various derivative regulations. The implementation of green tourism, in this case in North Sulawesi, has not been fully carried out successfully. This research can serve as input for aligning regulations and the issuance of Regional Regulations on Sustainable Tourism. The analysis technique in this study uses a descriptive method by first presenting the data, then analyzing it, and subsequently drawing conclusions. The concept of green tourism is aligned with the vision and mission of tourism law in general, and is part of the implementation of sustainable tourism development in Indonesia. The legal basis already exists, but there is a need to issue specific regulations focused on green tourism, implement a mandatory certification system, utilize green technology, and apply a digital/online monitoring system to oversee the implementation of sustainable tourism.